Leadership styles and labor engagement in credit analysts of the financial sector in Arequipa - Arias-Gonzáles, José (2021)
Objective. Determine the relationship between "leadership styles" and "work engagement" of credit analysts in companies in the financial sector in Arequipa, 2020. Methods. A basic study was carried out, with a correlational scope and a non-experimental-cross-sectional design. The population consisted of 268 credit analysts and the non-probabilistic sampling was used to establish the sample that was set at 253 credit analysts. The technique used was the survey and the instruments were the CELID-A questionnaire and the UWES scale. Results. The results show that the transactional leadership style is significantly related to a high level of "work engagement" (p-value = 0.00). Laissez faire leadership style is significantly related to a low level of "work engagement" (0.01) and transformational leadership style is not related to "work engagement" (0.13). Conclusions. There is a relationship between “leadership styles” and “work engagement” of credit analysts in companies in the financial sector.